2013
DOI: 10.1556/achrom.25.2013.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Rapid extraction, isolation, and quantification of oleanolic acid fromLantana camaraL. Roots using microwave and HPLC-PDA techniques

Abstract: Summary. An ecofriendly solvent polarity based microwave-assisted extraction (MAE) technique was developed for the rapid extraction and isolation of bioactive oleanolic acid from roots of Lantana camara L. Several different influential extraction parameters such as microwave power, extraction time, solvent type, and volume were studied in a systematic fashion for the determination of optimum extraction conditions. Simply modified and rapid high-performance liquid chromatography-diode array detector (HPLC-DAD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…The obtained thermogram exhibited a single endothermic peak at 309 °C. More recently, several authors have reported OA melting points in the range 306–313 °C [ 1 , 4 ]. The OA boiling temperature has been established at 553–554 °C at 760 mmHg ( , accessed on 18 November 2021).…”
Section: Oleanolic Acid Characterizationmentioning
confidence: 99%
“…The obtained thermogram exhibited a single endothermic peak at 309 °C. More recently, several authors have reported OA melting points in the range 306–313 °C [ 1 , 4 ]. The OA boiling temperature has been established at 553–554 °C at 760 mmHg ( , accessed on 18 November 2021).…”
Section: Oleanolic Acid Characterizationmentioning
confidence: 99%
“…Analytical equipment such as thin layer chromatography (TLC) [ 21 ], High Performance Liquid Chromatography (HPLC) [ 22 , 27 ] and nuclear magnetic resonance (NMR) [ 29 ] are common platforms that have been used in the characterization and identification of OA. Isolation of OA usually involves defatting of the pulverized powder of the plant with a non-polar solvent such as n -hexane [ 30 ] or petroleum ether [ 26 ]. This is typically followed by preparation of the crude extracts, and the isolation of oleanolic acid using techniques such as precipitation and crystallization [ 21 ], vacuum liquid chromatography [ 29 ] and column chromatography [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent examples are reported below. HPLC (or reversed-phase RP-HPLC) with various detector modes (UV, evaporative light scattering detection, photodiode array detection) appeared as the most employed technique for quantitation of UA and/or OA in plant extracts from Lantana camara [19], Salvia chinensis [20], Thymus ssp [21], and Nyctanthes arbor-tristis [22]. Otherwise, co-quantitation of OA and UA was achieved by LC-MS in oregano ( Origanum spp.)…”
Section: Introductionmentioning
confidence: 99%